Dabigatran Reversal Before Intravenous Tenecteplase in Acute Ischemic Stroke. Issue 5 (May 2020) - Beharry, James; Waters, Michael J.; Drew, Roy; Fink, John N.; Wilson, Duncan; Campbell, Bruce C.V.; Parsons, Mark W.; Kleinig, Timothy J.; Wu, Teddy Y.
Abstract : Background and Purpose—: Reversal of dabigatran before intravenous thrombolysis in patients with acute ischemic stroke has been well described using alteplase but experience with intravenous tenecteplase is limited. Tenecteplase seems at least noninferior to alteplase in patients with intracranial large vessel occlusion. We report on the experience of dabigatran reversal before tenecteplase thrombolysis for acute ischemic stroke. Methods—: We included consecutive patients with ischemic stroke receiving dabigatran prestroke treated with intravenous tenecteplase after receiving idarucizumab. Patients were from 2 centers in New Zealand and Australia. We reported the clinical, laboratory, and radiological characteristics and their functional outcome. Results—: We identified 13 patients receiving intravenous tenecteplase after dabigatran reversal. Nine (69%) were male, median age was 79 (interquartile range, 69–85) and median baseline National Institutes of Health Stroke Scale score was 6 (interquartile range, 4–21). Atrial fibrillation was the indication for dabigatran therapy in all patients. All patients had a prolonged thrombin clotting time (median, 80 seconds [interquartile range, 57–113]). Seven patients with large vessel occlusion were referred for endovascular thrombectomy, 2 of these patients (29%) had early recanalization with tenecteplase abrogating thrombectomy. No patients had parenchymal hemorrhage or symptomatic hemorrhagic transformation. Favorable functional outcome (modified Rankin Scale score, 0–2) occurred in 8 (62%) patients. Two deaths occurred from large territory infarction. Conclusions—: Our experience suggests intravenous thrombolysis with tenecteplase following dabigatran reversal using idarucizumab may be safe in selected patients with acute ischemic stroke. Further studies are required to more precisely estimate the efficacy and risk of clinically significant hemorrhage. Abstract : Supplemental Digital Content is available in the text.